Influence of welding parameters of resistance spot welding on joining aluminum with copper - Sar, Mohammed Helan; Ridha, Munaf Hashim; Barrak, Osamah Sabah; Hussein, Sabah Khammass (Zielona Góra: Uniwersytet Zielonogórski)
The resistance spot welding (RSW) method was used to join aluminum alloy AA 1050 and copper alloy UNS C50100 sheets. Mechanical properties of the joints were examined. The influence of welding process parameters on tensile shear force of the joints was discussed. The design of experiments (DOE) method was used to analyze the influence of welding parameters on the mechanical properties of the joints.
Keywords: resistance spot welding (RSW); aluminium; copper; RSW parameter; DOE